Comparison of lipid and lipoprotein values of wrestlers and soccer players - Cetin, S.; Ece, C.; Paksoy, M.; Cetin, H. N. (Turkish Journal of Pharmaceutical Sciences, 2020)
Objectives: The aim of this study was to compare the lipid and lipoprotein values of wrestlers and soccer players.Materials and Methods: A total of 35 subjects, 17 male wrestlers who are sporting for 11.5 years and 18 male soccer player students who are sporting for 11.9 years, participated in this study. Triglyceride (TG), total cholesterol (TC), high-density lipoprotein cholesterol (HDL-C), and low-density lipoprotein cholesterol (LDL-C) levels were determined by Hitachi 717 autoanalyzer. To determine the differences between the wrestlers and the soccer players the independent t-test was performed.Results: There was a significant difference in body weight and body mass index between the wrestlers and the soccer players (p<0.05). Moreover, there were significant differences in plasma TC, LDL-C, and HDL-C values between the wrestlers and soccer players (all, p<0.05). However, there was no significant difference in plasma TG values between the wrestlers and the soccer players (p>0.05). On the other hand, TC and LDL-C values of the wrestlers were significantly higher than soccer players (p<0.05). The HDL-C values of the soccer players were significantly higher the wrestlers (p<0.05). The ratio TC/HDL-C of the wrestlers was markedly higher than soccer players (p<0.05). Conclusion: TC, TG, HDL-C, and LDL-C values of the soccer players were in better ranges than wrestlers. This situation can be caused by the effect of different sports branches as well as the training differences. The lipid and lipoprotein values of the wrestlers and soccer players showed that they do not carry a risk of cardiovascular disease. In addition, it can be recommended that wrestlers should do jogging or aerobic training in their daily regular training.